2014
DOI: 10.3109/01902148.2014.946630
|View full text |Cite
|
Sign up to set email alerts
|

Krypton-enhanced ventilation CT with dual energy technique: Experimental study for optimal krypton concentration

Abstract: It is feasible to evaluate lung ventilation function using DECT with a krypton concentration of at least 70%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…Hence, we hypothesized that DE CT with the material decomposition method could differentiate krypton and iodine even when they are simultaneously used as contrast agents because the atomic number of 36 for krypton greatly differs from that of 53 for iodine, in contrast with nearby atomic numbers of 53 for iodine and 54 for xenon. In addition, krypton has been safely used as a radioactive nuclide in scintigraphy as a ventilation agent (26), and prior studies with conventional CT or DE CT have demonstrated its use as a radiographic inhalation contrast agent in human and animal subjects (24,(27)(28)(29). In our experimental study, iodine did not seem to be influenced by krypton on mixed-contrast agent CT, because we obtained similar results for the iodine map analysis for both mixed-contrast agent CT and iodine CT.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Hence, we hypothesized that DE CT with the material decomposition method could differentiate krypton and iodine even when they are simultaneously used as contrast agents because the atomic number of 36 for krypton greatly differs from that of 53 for iodine, in contrast with nearby atomic numbers of 53 for iodine and 54 for xenon. In addition, krypton has been safely used as a radioactive nuclide in scintigraphy as a ventilation agent (26), and prior studies with conventional CT or DE CT have demonstrated its use as a radiographic inhalation contrast agent in human and animal subjects (24,(27)(28)(29). In our experimental study, iodine did not seem to be influenced by krypton on mixed-contrast agent CT, because we obtained similar results for the iodine map analysis for both mixed-contrast agent CT and iodine CT.…”
Section: Discussionsupporting
confidence: 67%
“…Afterward, krypton maps were obtained from krypton CT with a modified prototype of the "Xenon" application class of the workstation, which was based on the material decomposition theory for xenon extraction from the lung parenchyma. We adjusted the material parameters for krypton extraction (Table 1) (24). Iodine maps were obtained from iodine CT with the "Lung PBV (Perfused Blood Volume)" application class of the workstation to extract iodine distribution from the lung parenchyma (Table 1).…”
Section: Image Analysismentioning
confidence: 99%